Numerical Simulation of Compositional Flow in Porous Media Under Gravity (Communications in Computational Physics, 2006)
This paper is concerned with the numerical simulation of multiphase, multicomponent flow in porous media. The model equations are based on compositional flowwith mass interchange between phases. The compositional model consists of Darcy'slaw for volumetric flow velocities, mass conservation for hydrocarbon components, thermodynamic equilibrium for mass interchange between phases, and an equation of statefor saturations. High-accurate finite volume methods on unstructured grids are used todiscretize the model governing equations. Special emphasis is placed on studying theinfluence of gravitational effects on the overall displacement dynamics. In particular,free and forced convections, diffusions, and dispersions are studied in separate and combined cases, and their interplays are intensively analyzed for gravitational instabilities.Extensive numerical experiments are presented to validate the numerical study underconsideration.
Keywords: Compositional model; reservoir simulation; finite volume method; unstructured grids; gravitational effect; free and forced convections; diffusions; dispersions; numerical experiments.